Sosialisasi dan Pendampingan PPh Pasal 21 di SMPN 15 Kabupaten Bengkulu Tengah - Rina Yuniarti; Junaidi, Ahmad; Sumarlan, Ahmad; Tezar Arianto; Riswandi, Pedi (Yayasan Literasi Sains Indonesia, 2024)
Income Tax 21 (PPh 21) is a tax obligation that must be well understood by teachers and administrative staff at schools. However, many teachers at SMPN 15 in Central Bengkulu Regency have not fully understood the procedures for calculating and reporting PPh 21, which could lead to administrative tax errors. Therefore, this community service activity aims to enhance the understanding and awareness of tax obligations among teachers and school staff through socialization and technical assistance regarding PPh 21. The methods used in this activity include observation, distribution of questionnaires, and technical assistance to ensure participants' understanding of how to calculate and report taxes. Evaluation was carried out using pre-tests and post-tests to measure the improvement in participants' knowledge of PPh 21. The results showed a significant increase in participants' understanding after attending this activity. This activity is expected to serve as a model for other schools in educating their teaching staff and administrative personnel about tax obligations.